Are Abbreviated Mental Test (AMT) and Ascertain Dementia 8 Indonesia (AD8-INA) Questionnaires More Superior than Mini-Mental State Examination (MMSE) as Dementia Screening Instrument among Elderly in Rural Areas? - Jovian Philip Swatan; Yudha Haryono (Universitas Airlangga, 2022)
Introduction: Dementia screening provides numerous benefits to its users. However, current screening methods have several limitations regarding applicability and accuracy, making it difficult to accommodate the results. Objective: To describe whether the Abbreviated Mental Test (AMT) and Ascertain Dementia 8 Indonesia (AD8-INA) questionnaire is superior to Mini-Mental State Examination (MMSE) questionnaire as a dementia screening instrument for the elderly in rural areas. Methods: A cross-sectional study was conducted in February 2020 at Banyuwangi residence. Dementia screening was conducted among elderly respondents using MMSE, AMT, and AD8-INA questionnaires. Sensitivity and specificity of AMT, AD8-INA and combined AMT+AD8-INA were compared with the MMSE questionnaire using crosstabs. Comparison of time required to complete each questionnaire was analyzed using Wilcoxon Signed Rank Test. Results: Mean age among 59 respondents was 68.44 years. The average MMSE score was 24.54. Compared with MMSE, the AMT questionnaire had a sensitivity of 47.37% and specificity of 100% (X2 = 22.36, p <0.001). Meanwhile, the AD8-INA questionnaire had a sensitivity of 63.16% and specificity of 45% (X2 = 24.64, p <0.001). The average questionnaire completion time of AMT, AD8-INA, and combined AMT+AD8-INA each was significantly shorter than MMSE (122.59, 121.17, and 243.76 seconds vs 319.83 seconds, p<0.001, <0.001, and <0.001, respectively). Conclusion: This study found that the combined AMT+AD8-INA questionnaire could be used as a dementia screening instrument among the elderly in rural areas with considerable sensitivity and shorter administration time.